Analysis Implementation of the Free Nutritious Meal Program (MBG) Policy in Indonesia (Edward III Implementation Model) - M. Rusdy Namsa (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
This study analyzes the implementation of the Free Nutritious Meal (MBG) program in Indonesia, a strategic national policy aimed at addressing stunting and malnutrition to support the